Formação Contínua em Serviço: o olhar do professor - Assis, Tatiana Pinheiro de [UNESP] (2014)
This report presents the research masters linked of the research line of Public Policy, School Organisation and Teacher Education, on Master's program in Education of the Faculty of Sciences and Technology - FCT - Universidade Estadual Paulista - UNESP, Presidente Prudente . The research’s object consists in a continuous training providing for the teachers of the Municipal Education System Araçatuba/SP which is entitled: Working Hours in Project’s Development and Research (HTPP). The subjects of this study are eleven teachers of a school for early childhood education of the mentioned education system. This research titled Training Continuous in Service: the look of the teacher brings as a general objective the analyze and reflection about the teachers’ vision/perception about the effects of HTPP program in the professional performance in the classroom. This guiding objective is deal with the common problem in the Brazil’s education system that refers to the following question: provide continuous training for teachers, often does not reflect significant changes in teaching practices and student learning. For this reason, we went to school listening to the teachers about how they evaluate the contributions provide by HTPP program for the educational process. One assumption is that continuous training program promotes the (re) construction of reflective and critical professional profile...